Relationship between job satisfaction and job performance among banking staffs at Standard Chartered Bank - Chan, Shiau Cin. (2009., 2009)
This study examines the relationships between job satisfaction and job performance among banking staff at Standard Chartered Bank. The sample consists of 80 banking staffs selected through the multi-stages sampling. The data collected via self administered questionnaire. The measurements of job satisfaction and job performance were adapted from Job descriptive Index (JDI) constructed by (Smith et al., 1969) and Job Performance measurement (Suliman's 18 Scale) respectively. Both instruments have highly reliable as Cronbach Alpha coefficients were above .90. The data obtained was analyzed using the Statistical Package for Social Science 12.0 Program. Descriptive statistics and Pearson Correlation were used to analyze the data in this study. Results shown that there was a significant and positive relationship between overall job satisfaction and job performance among banking staffs (r = .238*, p<0.05). It indicates that high level of job satisfaction were associated with high level of job performance. For the relationship between facets of job satisfaction and job performance among banking staffs at Standard Chartered Bank, the results indicated that among the five dimension of job satisfaction (work itself, supervision, co-worker, pay and opportunity for promotion) there were a significant relationships between the works itself with the job performance (r = .268*, p<0.05). In additional, there were also significant relationships between supervision and job performance (r = .314**, p<0.01). In contrast, from the results findings of job satisfaction and job performance at facets level, it indicates that there were no significant relationships between the co-worker, pay and opportunity for promotion with the job performance. Interestingly, among the five facets (work itself, supervision, co-worker, pay and opportunity for promotion) of the job satisfaction itself, there was a significant inter-relationship between each of the dimensions. With this study, it can provide the information to banking sectors that which factors will contributes to the satisfaction and dissatisfaction among the banking staff and how these will affect their productivity.
Project paper B.S.(H.D.M.) - Universiti Putra Malaysia, 2009.